2008
DOI: 10.1007/s00464-008-0079-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of gastrojejunal anastomoses with or without buttressing in a porcine model

Abstract: The addition of BSG as a staple-line reinforcement acutely improves the burst strength of a circular anastomosis but not at 1 week. At 1 week, a decrease in collagen content with the BSG-buttressed stapled anastomosis was the only difference in the histologic parameters studied with no difference in vascularity, adhesions, or inflammation. The long-term effect of BSG on anastomotic strength or scarring is yet to be determined. The clinical implications may include decreased stricture formation and also decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
(45 reference statements)
1
8
0
1
Order By: Relevance
“…A report on the long-term effect of buttressing by Hope et al [12] histologically and mechanically analyzed circular stapled anastomoses with and without bioabsorbable staple-line reinforcement. The addition of reinforcement acutely improves the burst strength of a circular anastomosis for the first postoperative week.…”
Section: Discussionmentioning
confidence: 99%
“…A report on the long-term effect of buttressing by Hope et al [12] histologically and mechanically analyzed circular stapled anastomoses with and without bioabsorbable staple-line reinforcement. The addition of reinforcement acutely improves the burst strength of a circular anastomosis for the first postoperative week.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Studies have shown reduced rates of bleeding and anastomosis leakage with its use in colon surgeries 14 and in appendectomies. 15 Lower rates of intraoperative bleeding, shorter surgical times, and reduced abscess formation with its use in bariatric surgery 16 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in strictures may be due to a reduction in tension at the staple line by the even distribution of forces over the area of buttressing material and decreased collagen formation seen when bovine pericardium reinforcement is used. 7,23 …”
Section: Discussionmentioning
confidence: 99%